Collusive practices in public procurement and the effects of the antitrust compliance and leniency program - García Coso, Emiliano (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This article focuses on the analysis of collusive practices in public procurement and the application of competition rules to protect the affected public interest, both in the European market and, especially, in the Spanish market. Bidding companies in public procurement may engage in secret cartels or “bid rigging,” which are difficult for contracting authorities and competition authorities to detect. Despite the reforms introduced in Spanish legislation to coordinate between contracting authorities and competition authorities and the adoption of a prohibition on contracting as a legal consequence, bid rigging continues to occur. Therefore, this paper analyzes the potential benefits that can be achieved by introducing an ex ante competition law compliance program for bidding companies, or “antitrust compliance,” which not only protects the public interest but also the bidding companies themselves and their responsible executives from the administrative sanctions associated with engaging in collusive practices. Finally, the use of leniency programs is addressed as a tool that facilitates investigations into collusive practices in public procurement, but which raises certain concerns for applicants due to its impact on private actions seeking damages.